Effect of soaking seeds of two tobacco varieties (Berley 21 and Virginia VK51) in chemical mutagen (EMS) on some growth indicators under drought stress conditions - مجد درويش; نزار معلا; احمد صوفي (Latakia University Journal -Biological Sciences Series, 2022)
The research was carried out during the 2021 to study the effect of treatment with the chemical mutagen Ethyl Methane Sulfonate (EMS) in improving the tolerance of two tobacco varieties (Burley 21 and Virginia VK51) to drought stress. The seeds were treated using three concentrations of the mutagen (0, 0.1, 0.5 and 1 %) with a soaking time of (8) hours. In addition, to induce drought stress, polyethylene glycol (PEG) was used at concentrations (15, 30 and 45 %) equivalent to an osmotic pressure (-0.52, -1.04 and -1.56) MPa. The experiment was conducted according to a randomized complete block design (RCBD) at the Bouqa farm of the Faculty of Agricultural Engineering-Tishreen University - Lattakia- Syria, and with three replications per treatment. Some germination characteristics for treated seeds (germination percentage (%) and germination speed (day) number of morphological indicators for plants (plant height (cm/plant), internode length (cm) and stem diameter (cm)) were also measured. Treatment with EMS at a low concentration (0.1) % led to an increase in the germination rate and speed of both tobacco varieties, High concentration of EMS at 1 % caused a decrease in the germination rate of 31 and 34% in the Burley and Virginia tobacco varieties, respectively. The chemical mutagen treatment under drought stress conditions at a low concentration (0.1) %, also improved the values of most of the studied indicators compared to the other treatments. The treatment with PEG at the high concentration, had a negative effects on the growth of both tobacco varieties. Thus, it can be suggested to soak seeds at the concentration 0.1% for its role in improving the germination of two tobacco varieties (Berley 21 and Virginia VK51).